A gallium nitride-based metal composite SERS chip and a preparation method and application thereof
Patent Information
- Application Number
- CN202611036578.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-09
AI Technical Summary
这种现象导致激光光斑区内的有效分子数量锐减,严重削弱了检测的灵敏度,并造成同一芯片不同测试点位的信号剧烈波动
(1)本发明提供了一种高性能的氮化镓基金属复合SERS芯片,该芯片在氮化镓表面独特设计了与常规拉曼光谱仪激光光斑尺寸高度匹配的周期性圆环阵列凸起结构;这种微米级(孔径1~2 μm)的微纳光学腔结构有效改变了传统平面或简单纳米阵列光场局域能力弱的缺陷,形成了显著的“光阱效应”,极大减少了入射激光在基底表面的反射与散射损耗,最大化了激光利用率。
Smart Images

Figure CN122882418A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of SERS material technology, and relates to a gallium nitride-based metal composite SERS chip, its preparation method and application. Background Technology
[0002] Surface-enhanced Raman scattering (SERS) is an ultra-sensitive molecular spectroscopy technique that provides characteristic "fingerprint" spectral information of molecules. It boasts advantages such as fast detection speed, small sample volume, and no need for complex pretreatment, making it promising for applications in biomedical detection, environmental pollutant monitoring, food safety screening, and public safety and security. Traditional SERS substrates primarily rely on electromagnetic enhancement (EM) generated by noble metal nanostructures such as gold and silver to amplify signals. However, pure noble metal substrates suffer from poor chemical stability, easy oxidation, and low biocompatibility. In recent years, wide-bandgap semiconductor materials, represented by gallium nitride (GaN), have become ideal candidates for SERS substrates due to their excellent chemical stability, good biocompatibility, and tunable band structure. Combining GaN with noble metal nanostructures can simultaneously generate a synergistic effect of electromagnetic enhancement and chemical enhancement (CM) induced by charge transfer at the semiconductor-metal interface, thereby significantly improving the overall performance of SERS.
[0003] However, existing gallium nitride-based metal composite SERS chips still face the following significant technical bottlenecks in practical applications: First, existing GaN-based SERS substrates are mostly planar structures or simple nanopillar / nanowire arrays. Planar structures have weak optical field localization capabilities; while conventional nanoarrays, although increasing the specific surface area, are not optically matched to the excitation spot of the Raman spectrometer in terms of structural size and arrangement. This leads to severe reflection and scattering losses of the incident laser on the substrate surface, preventing the optical field from achieving maximum localization and enhancement in the detection area, and thus failing to fundamentally improve laser utilization efficiency.
[0004] Secondly, current methods for preparing GaN-based metal composite substrates typically employ physical vapor deposition (PVD) methods such as magnetron sputtering and electron beam evaporation to directly deposit metal films on the GaN surface, followed by annealing to form metal nanoparticles. Due to the lattice mismatch and surface energy differences on the GaN surface, the metal nanoparticles formed by this method often suffer from uneven nucleation, wide size distribution, and severe agglomeration. This uncontrollable growth process results in extremely random distribution of SERS "hot spots," leading not only to significant signal differences between chip batches but also to the tendency for metal nanoparticles to detach or change morphology during prolonged use or in complex environments, severely impacting the long-term stability and reproducibility of the SERS signal.
[0005] Furthermore, in actual testing, the samples to be tested are often trace amounts of aqueous solutions. Unmodified GaN substrates are typically hydrophilic, and when trace drops are added to the substrate surface, they spread rapidly, leading to a significant dilution of the analyte concentration in certain areas. More seriously, during the natural evaporation of the solvent, the hydrophilic surface is prone to the "coffee-ring effect," causing analyte molecules to migrate with the capillary flow and accumulate at the edge of the droplet, while the central region of the droplet (which is usually the focusing area of the Raman laser spot) is extremely deficient in analyte molecules. This phenomenon results in a sharp reduction in the number of effective molecules within the laser spot area, severely weakening the detection sensitivity and causing drastic signal fluctuations at different test points on the same chip.
[0006] In summary, developing a GaN-based SERS chip with high Raman signal intensity, high uniformity, and high stability is a technical challenge that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0007] To address the aforementioned problems in the prior art, the present invention aims to provide a gallium nitride-based metal composite SERS chip, its fabrication method, and its applications, thereby overcoming the shortcomings of the prior art.
[0008] The present invention employs the following technical solutions to achieve its objective: One aspect of the present invention provides a gallium nitride-based metal composite SERS chip, comprising a gallium nitride substrate, wherein the surface of the gallium nitride substrate is provided with a periodically arranged circular array of protrusions; a two-dimensional monolayer gold nanoparticle film is attached to the surface of the gallium nitride substrate and the circular array of protrusions. The periodically arranged circular array of bumps includes multiple circular bumps, each with an outer diameter of 3~6μm, a central hole diameter of 1~2μm, and a height of 200~1000nm relative to the gallium nitride substrate surface. The two-dimensional monolayer gold nanoparticle film is prepared by liquid-liquid interface self-assembly process and then transferred and bonded to the surface of the gallium nitride substrate and the annular array protrusion structure.
[0009] The thickness of the gallium nitride substrate is 1~10 μm. In practical applications, the gallium nitride substrate can be a single-material independent gallium nitride substrate; or it can be a composite substrate structure, that is, it is composed of a sapphire underlayer and a gallium nitride thin film epitaxially grown on the surface of the sapphire underlayer.
[0010] The periodically arranged circular array of protrusions includes multiple circular protrusions. In this paper, "multiple" can be, for example, ≥2, ≥10, ≥100, ≥1000, or values such as 10, 100, 1000, 10000, 100000, 1000000, 1000000, 1000000, 10000000, etc.
[0011] Preferably, the distance between two adjacent annular protrusions is 2~6μm; the distance between two adjacent annular protrusions is defined as the minimum distance between any two points on the boundary of the two annular protrusions.
[0012] Preferably, the average particle size of the gold nanoparticles in the two-dimensional monolayer gold nanoparticle film is 10~80 nm. The thickness of the two-dimensional monolayer gold nanoparticle film is approximately equal to the particle size of a single gold nanoparticle.
[0013] The liquid-liquid interface self-assembly process includes the following steps: adding a solution containing an assembly agent to an aqueous solution of gold nanoparticles, and forming a two-dimensional monolayer gold nanoparticle film at the liquid-liquid interface by utilizing the principle of liquid-liquid interface self-assembly.
[0014] Preferably, the solution containing the assembling agent is formed by dissolving the assembling agent in an organic solvent, wherein the assembling agent is 1H,1H,2H,2H-perfluorodecyl mercaptan (PFT) and / or dodecyl mercaptan (DDT), and the organic solvent is obtained by mixing ethanol and n-hexane in a volume ratio of 1:0.2~2, and the concentration of the assembling agent in the solution is 1~100 mmol / L.
[0015] Preferably, the surface of the gallium nitride-based metal composite SERS chip further has a hydrophobic modification layer, which is composed of one or more of perfluorodecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, perfluorooctyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.
[0016] A second aspect of this invention provides a method for fabricating the above-mentioned gallium nitride-based metal composite SERS chip, comprising the following steps: S1. A periodically arranged ring array of protrusions is prepared on the surface of a gallium nitride thin film by photolithography combined with etching process; S2. A solution containing an assembly agent is added to an aqueous solution of gold nanoparticles. A two-dimensional monolayer gold nanoparticle film is formed at the liquid-liquid interface by utilizing the self-assembly principle of the liquid-liquid interface. S3. The two-dimensional monolayer gold nanoparticle film is transferred from the liquid phase interface to the surface of the gallium nitride substrate and the annular array protrusion structure to obtain a composite SERS chip.
[0017] Step S1 specifically includes: (1) Photomask preparation: Design a photomask with a circular array pattern. The circular array pattern is composed of multiple periodically arranged circular structural units. The outer diameter of a single circular structural unit is 3~6 μm, and a circular hollow hole with a diameter of 1~2 μm is provided in the center. The spacing between two adjacent circular structural units (the spacing is defined as the minimum distance between any two points on the boundary of two circular structural units) is 2~6 μm. The circular rings in the photomask are opaque, while the rest of the area is transparent. (2) Photolithography process: Photoresist is coated on the surface of the gallium nitride thin film. After spin coating, pre-baking treatment is performed. A photolithography machine is used to bond the photomask and the photoresist layer together to complete the exposure. After exposure, the photomask is removed, the sample is immersed in the developing solution for development, and after being taken out, it is rinsed and dried to form a photoresist ring array mask on the surface of the gallium nitride thin film. (3) Etching and photoresist removal: Dry etching is performed using a plasma etching machine with an etching depth of 200~1000nm. Only the circular area covered by photoresist is retained. After etching, photoresist removal and cleaning are performed. After drying, gallium nitride with a periodically arranged circular array of protrusions on the surface is obtained.
[0018] Preferably, the thickness of the gallium nitride thin film is 1.2~11 μm, and the gallium nitride thin film is etched to obtain a gallium nitride substrate with a thickness of 1~10 μm.
[0019] Preferably, in step (2) above, the spin coating process involves first spin coating at a speed of 600~1000 rpm for 12 s, and then spin coating at a speed of 2000~4000 rpm for 30~50 s; the pre-baking treatment involves placing the sample on a hot plate at 90~100 ℃ and heating it for 80~100 s; the exposure dose is 100~150 mJ / cm 2 The development time is 60-90 seconds. After development, rinse with flowing ultrapure water and dry with high-purity nitrogen.
[0020] In step (3), the photoresist removal cleaning is specifically as follows: the sample is immersed in an N-methylpyrrolidone solution heated to 70~90 ℃ for 10~40 min to remove the photoresist, then transferred to an isopropanol solution for 5~20 min, and finally placed in deionized water for ultrasonic cleaning for 5~20 min. After removal, it is dried with high-purity nitrogen gas.
[0021] Preferably, the concentration of the gold nanoparticle aqueous solution is 50~500 μg / mL, and the average particle size of the gold nanoparticles in the aqueous solution is 10~80 nm.
[0022] The preparation method of the gold nanoparticle aqueous solution is not limited, and any method that can prepare gold nanoparticles with an average particle size of 10-80 nm is within the protection scope of this invention. As an example, the gold nanoparticle aqueous solution is prepared using the sodium citrate reduction method, specifically including the following steps: (1) Prepare chloroauric acid solution and sodium citrate solution; (2) Mix the chloroauric acid solution with water and bring it to a boil under heating and stirring conditions; (3) Quickly add the sodium citrate solution to the boiling solution and continue heating the reaction; (4) After the reaction is complete, cool naturally to room temperature to obtain an aqueous solution of gold nanoparticles.
[0023] Step S3 specifically includes: immersing the gallium nitride substrate with the annular array protrusion structure prepared in step S1 into the liquid of step S2, lifting the two-dimensional monolayer gold nanoparticle film from bottom to top at the liquid phase interface, and then applying a pressure of 0.3~0.8 N on the film surface and holding it for 5~40 s.
[0024] Preferably, the surface of the gallium nitride-based metal composite SERS chip further has a hydrophobic modification layer, and the preparation method further includes: S4. The hydrophobic modifier is used to hydrophobically modify the surface of the composite SERS chip with a transferred gold nanoparticle film by vapor deposition. The specific preparation method includes the following steps: the composite SERS chip and the glass slide carrying the hydrophobic modifier are placed together in a vacuum drying oven and heated at 100~120℃ for 2~8 h, and then cooled to obtain the hydrophobic modified layer.
[0025] The hydrophobic modifier is one or more of perfluorodecyltrimethoxysilane, tridecylfluorooctyltriethoxysilane, perfluorooctyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.
[0026] A third aspect of the present invention provides the application of the gallium nitride-based metal composite SERS chip in surface-enhanced Raman spectroscopy detection.
[0027] A fourth aspect of the present invention provides a semiconductor device, including a gallium nitride-based metal composite SERS chip.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention provides a high-performance gallium nitride-based metal composite SERS chip. The chip has a uniquely designed periodic circular array protrusion structure on the gallium nitride surface that is highly matched with the laser spot size of conventional Raman spectrometers. This micron-scale (aperture 1~2 μm) micro-nano optical cavity structure effectively changes the defect of weak localization ability of traditional planar or simple nano arrays, forming a significant "optical trap effect", which greatly reduces the reflection and scattering loss of incident laser on the substrate surface and maximizes the laser utilization rate.
[0029] (2) This invention successfully bonded a two-dimensional monolayer gold nanoparticle film to the surface of a three-dimensional ring array with high fidelity by combining "liquid-liquid interface self-assembly" with "pressure transfer" process. Compared with the problems of uneven nucleation, wide size distribution and agglomeration of metal particles that are easily caused by direct physical film deposition followed by annealing, this invention pre-constructs a dense and uniformly spaced monolayer gold film at the liquid phase interface, and then achieves conformal bonding between the gold film and the inner wall of the three-dimensional ring through pressure transfer. The synergistic effect of the three-dimensional confinement effect and the optical trap enhancement potential of the uniform monolayer gold film simultaneously achieves a dual improvement in SERS sensitivity and signal reproducibility.
[0030] (3) The chip prepared by the present invention not only has a significant increase in the intensity of Raman characteristic peaks, but also has a signal relative standard deviation (RSD) as low as 4.21%, which solves the problem of high randomness and poor reproducibility of traditional SERS substrate signals.
[0031] (4) In the preparation process of this invention, a hydrophobic modification layer is preferably introduced on the chip surface by vapor deposition, which can effectively limit droplet spreading, suppress the "coffee ring effect", and promote the analyte molecules to be efficiently enriched towards the droplet center (i.e., the laser focusing area) under the action of capillary force, thereby multiplying the effective number of molecules and Raman signal in actual detection. Attached Figure Description
[0032] Figure 1 The images shown are characterization images of the gold nanoparticle interface film in Example 1, where (A) is an optical image of the gold nanoparticle aqueous solution; (B) is an optical image of the gold nanoparticle interface film; and (C) is a SEM image of the gold nanoparticle film.
[0033] Figure 2 The images show SEM images of the n-GaN array structure before and after the transfer of gold nanoparticle films, as well as EDS elemental distribution diagrams of the n-GaN array structure after transfer. Among them, (A) is a low-magnification SEM image of the n-GaN ring array, (B) is a SEM image of a single n-GaN ring structure, (C) is a SEM image of a single n-GaN ring structure after the transfer of gold nanoparticle films, (D) shows the distribution of Au and Ga elements, (E) shows the distribution of single-element Au, and (F) shows the distribution of single-element Ga.
[0034] Figure 3 These are contact angle test images of the n-GaN / Au NPs composite SERS chip surface before and after hydrophobic modification. (A) shows the contact angle of the n-GaN / Au NPs composite SERS chip without hydrophobic modification, and (B) shows the contact angle of the n-GaN / Au NPs composite SERS chip after hydrophobic modification.
[0035] Figure 4 The images show a comparison of the Raman spectra of the SERS chips prepared in Example 1 and Comparative Examples 1-3, where (A) is a comparison of the Raman spectra of the SERS chips prepared in Example 1 and Comparative Examples 1-3 under the same conditions; (B) is a comparison of the Raman spectra of the chips prepared in Example 1 and Comparative Examples 1-3 at 610 cm⁻¹. -1 A histogram comparing the average signal intensity at characteristic peak positions.
[0036] Figure 5 The SERS chips prepared for Examples 1 and Comparative Examples 1-3 were tested at 10 random test points, and the probe molecule R6G was observed at 610 cm⁻¹. -1 The RSD statistics of the characteristic peak intensity are shown in (A) for Example 1, (B) for Comparative Example 3, (C) for Comparative Example 1, and (D) for Comparative Example 2. Detailed Implementation
[0037] In the description of this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, and includes both a and b. "Multiple" includes two or more types, and can be two, three, four, five, or more.
[0038] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.
[0039] Example 1
[0040] The high-performance SERS chip provided in this embodiment is prepared by the following steps: Step S1: Fabrication of gallium nitride ring array bump structure (1) Mask design and substrate preparation: A circular array pattern was designed using KLayout software, and a photomask was fabricated. The circular array pattern consisted of approximately 4 × 10⁻⁶ pixels. 5 It consists of periodically arranged circular ring structure units, each with an outer diameter of 4 μm and a central circular hole with a diameter of 1.5 μm. The spacing between two adjacent ring structure units is 4 μm. The rings themselves are opaque on the photomask, while other areas are transparent. A sapphire substrate is selected as the substrate, on which a 2 μm thick n-type gallium nitride (n-GaN) thin film is epitaxially grown.
[0041] (2) Photolithography process: The n-GaN surface was spin-coated with photoresist, using AZ5214 positive photoresist. The spin-coating parameters were: spin-coating at 800 rpm for 12 s, followed by spin-coating at 3000 rpm for 40 s. After spin-coating, the sample was pre-baked on a hot plate at 100 ℃ for 90 s. Subsequently, a contact lithography machine was used in hard contact mode to ensure close contact between the photomask and the n-GaN surface photoresist layer for exposure, with an exposure dose of 125 mJ / cm². 2 After exposure, the photomask is removed, and the sample is immersed in the developer for 70 seconds to remove the photoresist in the exposed area. Immediately after development, the sample is removed, rinsed with running ultrapure water, and dried with high-purity nitrogen. This yields an n-GaN substrate with a photoresist ring array mask.
[0042] (3) Etching and photoresist removal process: The developed n-GaN was dry etched using a plasma etching machine to a depth of 500 nm (only the solid ring region covered by photoresist on the n-GaN surface was completely preserved, and other areas were etched to a depth of 500 nm). After etching, photoresist removal was performed: the sample was immersed in an N-methylpyrrolidone (NMP) solution heated to 80 °C for 30 min to remove the photoresist; then the sample was transferred to an isopropanol (IPA) solution for 10 min; finally, the sample was ultrasonically cleaned in deionized water for 10 min, and then dried with high-purity nitrogen to obtain a gallium nitride ring array bump structure. The sample substrate structure from top to bottom is: sapphire substrate + 1.5 μm thick n-GaN bottom layer + 500 nm high hollow ring array bump structure.
[0043] Step S2: Preparation of gold nanoparticle interface film (1) Synthesis of aqueous solution of gold nanoparticles (Au NPs): Prepared by sodium citrate reduction method. Prepare 5 mM chloroauric acid solution; weigh 0.1 g sodium citrate, dissolve in 10 mL deionized water to prepare sodium citrate solution with a concentration of 1 g / 100 mL. Take 10 mL of the above chloroauric acid solution and mix with 40 mL of deionized water and transfer to a round bottom flask. Heat in an oil bath at 120 ℃ and stir magnetically. After the solution boils, quickly add 2.5 mL of the above sodium citrate solution and continue the reaction for 20 min. After the reaction is completed, cool naturally to room temperature to obtain an aqueous solution of gold nanoparticles with a concentration of about 200 μg / mL and an average particle size of 30~40 nm. Take 2.5 mL of the above solution, add 2.5 mL of deionized water to dilute to obtain 5 mL of gold nanoparticle dilution with a concentration of 100 μg / mL, and place in a beaker for later use.
[0044] (2) Interfacial self-assembly to form a film: 48 mg of 1H,1H,2H,2H-perfluorodecylthiol (PFT) was dissolved in 10 mL of a mixed solvent of ethanol and n-hexane (6.67 mL of ethanol and 3.33 mL of n-hexane) to prepare a 10 mM PFT solution. The PFT solution was quickly poured into a beaker containing a gold nanoparticle dilution solution, and immediately manually shaken for about 3 s, followed by standing for 2 s (total operation time controlled within 5 s). Utilizing the principle of liquid-liquid interface self-assembly, a dense and uniform two-dimensional monolayer gold nanoparticle film (thickness close to that of a single gold nanoparticle) was formed at the n-hexane-water interface.
[0045] Step S3: Transfer of gold nanoparticle interface film The gallium nitride (GaN) ring array bump structure chip prepared in step S1 is lifted from the hexane-water interface from bottom to top, allowing the film to adhere to the surface of the GaN ring array bump structure. Subsequently, a uniform pressure of 0.5 N is applied to the film surface and held for 15 s to ensure tight bonding between the gold nanoparticle film and the GaN surface, achieving complete transfer of the gold nanoparticle film and obtaining a GaN / Au NPs composite SERS chip.
[0046] Step S4: Hydrophobic modification of GaN / Au NPs composite SERS chip Hydrophobic modification of the composite substrate was performed using vapor deposition: The GaN / Au NPs composite substrate and a clean glass slide were placed together in a vacuum desiccator, and four drops of perfluorodecyltrimethoxysilane were added to the glass slide as a hydrophobic modifier. The vacuum desiccator was evacuated, and then placed in a vacuum drying oven and heated at 110 °C for 5 h to allow the hydrophobic modifier to be uniformly deposited on the chip surface in vapor phase. After heating, the substrate was allowed to cool naturally to room temperature, and the hydrophobically modified GaN / Au NPs composite SERS chip was obtained.
[0047] Example 2
[0048] The high-performance SERS chip provided in this embodiment is prepared by the following steps: Step S1: Fabrication of gallium nitride ring array bump structure (1) Mask design and substrate preparation: A circular array pattern was designed using KLayout software, and a photomask was prepared. The circular array pattern consisted of multiple periodically arranged circular structural units. The outer diameter of each circular structural unit was 5 μm, and a circular hole with a diameter of 2 μm was provided in the center. The spacing between two adjacent circular structural units was 4 μm. The circular rings on the photomask were opaque, while other areas were transparent. A sapphire substrate was selected as the substrate, on which a 3 μm thick n-type gallium nitride (n-GaN) thin film was epitaxially grown.
[0049] (2) Photolithography process: The n-GaN surface was spin-coated with photoresist, using AZ5214 positive photoresist. The spin-coating parameters were: spin-coating at 800 rpm for 10 s, followed by spin-coating at 3500 rpm for 50 s. After spin-coating, the sample was pre-baked on a hot plate at 100 ℃ for 80 s. Subsequently, a contact lithography machine was used in hard contact mode to tightly bond the photomask to the n-GaN surface photoresist layer for exposure, with an exposure dose of 130 mJ / cm². After exposure, the photomask was removed, and the sample was immersed in the developer for 80 s. The photoresist in the exposed area was removed. After development, the sample was immediately removed, rinsed with flowing ultrapure water, and dried with high-purity nitrogen. An n-GaN substrate with a photoresist ring array mask was obtained.
[0050] (3) Etching and photoresist removal process: The developed n-GaN was dry etched using a plasma etching machine to a depth of 600 nm (only the solid ring region covered by photoresist on the n-GaN surface was completely preserved, and other areas were etched to a depth of 600 nm). After etching, photoresist removal was performed: the sample was immersed in an N-methylpyrrolidone (NMP) solution heated to 90 °C for 40 min to remove the photoresist; then the sample was transferred to an isopropanol (IPA) solution for 20 min; finally, the sample was ultrasonically cleaned in deionized water for 20 min, and then dried with high-purity nitrogen to obtain a gallium nitride ring array bump structure. The sample substrate structure from top to bottom is: sapphire substrate + 2.4 μm thick flat n-GaN bottom layer + 600 nm high hollow ring array bump structure.
[0051] Step S2: Preparation of gold nanoparticle interface film (1) Synthesis of gold nanoparticles (Au NPs) aqueous solution: prepared by sodium citrate reduction method. Prepare 6 mM chloroauric acid solution; weigh 0.2 g sodium citrate, dissolve in 10 mL deionized water to prepare a sodium citrate solution with a concentration of 2 g / 100 mL. Take 10 mL of the above chloroauric acid solution and mix with 40 mL of deionized water and transfer to a round bottom flask. Heat in an oil bath at 110 ℃ and stir magnetically. After the solution boils, quickly add 1.5 mL of the above sodium citrate solution and continue the reaction for 30 min. After the reaction is completed, cool naturally to room temperature to obtain an aqueous solution of gold nanoparticles with a concentration of about 250 μg / mL and an average particle size of 30~40 nm. Take 2.5 mL of the above solution and dilute with 2.5 mL of deionized water to obtain 5 mL of gold nanoparticle dilution with a concentration of 125 μg / mL, and place it in a beaker for later use.
[0052] (2) Interfacial self-assembly to form a film: 48 mg of perfluorodecyl mercaptan (PFT) was dissolved in a mixed solvent of 12 mL ethanol and n-hexane (8 mL ethanol and 4 mL n-hexane) to prepare a PFT solution. The PFT solution was quickly poured into a beaker containing a gold nanoparticle dilution solution, and immediately manually shaken for about 3 s, followed by standing for 2 s (total operation time controlled within 5 s). Utilizing the principle of liquid-liquid interface self-assembly, a dense and uniform two-dimensional monolayer gold nanoparticle film was formed at the n-hexane-water interface.
[0053] Step S3: Transfer of gold nanoparticle interface film The gallium nitride (GaN) ring array bump structure chip prepared in step S1 is lifted from the hexane-water interface from bottom to top, allowing the film to adhere to the surface of the GaN ring array bump structure. Subsequently, a uniform pressure of 0.5 N is applied to the film surface and held for 20 s to ensure a tight bond between the gold nanoparticle film and the GaN surface, achieving complete transfer of the gold nanoparticle film and obtaining a GaN / Au NPs composite SERS chip.
[0054] Step S4: Hydrophobic modification of GaN / Au NPs composite SERS chip Hydrophobic modification of the composite substrate was performed using vapor deposition: The GaN / Au NPs composite substrate and a clean glass slide were placed together in a vacuum desiccator, and four drops of tridecafluorooctyltriethoxysilane were added to the glass slide as a hydrophobic modifier. The vacuum desiccator was evacuated, and then placed in a vacuum drying oven and heated at 110 °C for 5 h to allow the hydrophobic modifier to be uniformly deposited on the chip surface in vapor phase. After heating, the substrate was allowed to cool naturally to room temperature, and the hydrophobically modified GaN / Au NPs composite SERS chip was obtained.
[0055] Comparative Example 1 The SERS chip without annular array bumps provided in Comparative Example 1, and its fabrication method via direct film deposition and annealing on the substrate, are as follows: Step S1: Select a sapphire substrate as the substrate, and epitaxially grow an n-type gallium nitride (n-GaN) thin film with a thickness of 2 μm on it.
[0056] Step S2: A gold film is deposited on the n-GaN surface by magnetron sputtering to obtain a GaN / Au NPs composite SERS chip. The deposition time is 40 s, and the Au film thickness is 35 nm. Then, it is annealed at 800 ℃ for 90 s to obtain the GaN / Au NPs composite SERS chip.
[0057] Step S3: A hydrophobic modifier is deposited on the chip surface using the hydrophobic modification step S4 of Example 1 to obtain a hydrophobically modified GaN / Au NPs composite SERS chip.
[0058] Comparative Example 2 The SERS chip provided in Comparative Example 2 is prepared by directly depositing and annealing a film on the substrate. The specific preparation method is as follows: Step S1 and the preparation method are the same as step S1 in Example 1, to obtain a gallium nitride ring array bump structure; Step S2: Using the same magnetron sputtering method as in Comparative Example 1, a gold film is deposited on the surface of the gallium nitride ring array protrusion structure to obtain a GaN / Au NPs composite SERS chip.
[0059] Step S3: A hydrophobic modifier is deposited on the chip surface using the hydrophobic modification step S4 of Example 1 to obtain a hydrophobically modified GaN / Au NPs composite SERS chip.
[0060] Comparative Example 3 The fabrication method of the SERS chip without annular array bumps provided in Comparative Example 3 is as follows: Step S1: Select a sapphire substrate as the substrate, and epitaxially grow an n-type gallium nitride (n-GaN) thin film with a thickness of 2 μm on it.
[0061] Steps S2, S3 and S4 are the same as steps S2, S3 and S4 in Example 1.
[0062] Experimental data analysis: 1. Preparation and characterization of gold nanoparticle interfacial films Figure 1 (A) is an aqueous solution of gold nanoparticles before the addition of PFT solution; such as Figure 1 As shown in (B), after adding PFT solution, gold nanoparticles successfully formed a large-area, dense film with obvious metallic luster at the hexane-water interface. Figure 1 The SEM image in (C) further confirms that the gold nanoparticles self-assemble at the interface to form a dense two-dimensional monolayer structure with particle sizes concentrated between 30 and 40 nm and an extremely uniform size distribution. Numerous and uniform nano-gap structures are formed between the particles, which will serve as high-density SERS electromagnetic enhancement "hot spots," demonstrating that the interface self-assembly method of this invention can prepare high-quality gold nanoparticle films.
[0063] 2. Morphological characterization of GaN / Au NPs composite SERS chip with gallium nitride ring array bump structure Figure 2 (A) and Figure 2 (B) is a SEM image of the gallium nitride ring array bump structure prepared in Example 1. Figure 2 (A) shows that, through optimized photolithography and plasma etching processes, a periodically arranged ring array of bumps was successfully fabricated on the surface of n-type gallium nitride. Figure 2 (B) It can be seen that the array unit size is uniform (outer diameter approximately 4 μm, central aperture approximately 1.5 μm), the morphology of the holes and walls is clear, the overall distribution is highly uniform, and there are no obvious structural defects. The size of the central hole of this specially made annular array protrusion structure matches the laser spot size of a conventional Raman spectrometer, providing an ideal micro-nano structure basis for maximizing laser utilization and enhancing the localization effect of the light field. Figure 2 (C) is a SEM image of the GaN / Au NPs composite SERS chip. Figure 2(D)-(F) are EDS images of the GaN / Au NPs composite SERS chip. The SEM and EDS images together show that the gold nanoparticle interface film was successfully transferred to the GaN surface.
[0064] 3. Verification of the hydrophobic modification effect on the chip surface Figure 3 Images show the water contact angle (CA) of the SERS chip surface before and after hydrophobic modification. The unmodified GaN / AuNPs composite SERS chip surface exhibits hydrophilicity. Figure 3 (A)); After modification by perfluorodecyltrimethoxysilane vapor deposition, the water contact angle on the chip surface significantly increased to 124° ( Figure 3 (B) exhibits excellent hydrophobic properties. This hydrophobic surface can effectively limit the spread of trace amounts of test droplets, suppress the "coffee ring effect" during solvent evaporation, and promote the efficient enrichment of test molecules towards the droplet center (i.e., the laser focusing area) under the action of capillary forces, thus laying a key interfacial foundation for improving the sensitivity of SERS detection.
[0065] 4. Performance Testing of GaN / Au NPs Composite SERS Chip To verify the inventiveness and substantial progress of the technical solution of this invention, a systematic Raman spectroscopy test (Horiba, LabRAM Odyssey) was performed on the prepared SERS chip. All Raman tests were conducted at room temperature, using Rhodamine 6G (R6G) aqueous solution as the probe molecule at a concentration of 1×10⁻⁶. -5 M, 3 μL of R6G was added to the chip using a pipette. Detection parameters were set as follows: excitation laser wavelength 532 nm, spot diameter 1.5 μm, objective lens magnification 50×; to avoid laser thermal effects damaging the probe molecules or causing signal saturation, the laser power was set to 3.2%, single-point integration time was 2 s, and the number of integrations was 2. To evaluate signal reproducibility, spectral acquisition was performed at 10 randomly selected locations for each chip. Specific comparative analysis is as follows: 4.1 Analysis of the Influence of Gold Nanoparticle Film Formation Process on SERS Sensitivity and Stability To verify the advantages of the "interface self-assembly into film followed by transfer" process of the present invention compared with the traditional "direct film deposition and annealing on the substrate" process, while keeping the substrate structure (both are circular array GaN) consistent, the SERS performance of Example 1 (interface transfer method) and Comparative Example 2 (traditional direct magnetron sputtering gold film deposition followed by high-temperature annealing into particles) were compared.
[0066] like Figure 4As shown in (A), the average Raman signal intensity of Example 1 is significantly higher than that of Comparative Example 2. This is because the direct deposition annealing method is limited by the surface energy and lattice mismatch of the GaN surface, and gold particles are prone to uncontrollable excessive agglomeration during the annealing process, resulting in a reduction in the number and size of effective nano-interstic gaps (hot spots); while the interface transfer method of the present invention pre-forms a dense and uniformly spaced monolayer gold film at the liquid-liquid interface, and perfectly retains the high-density uniform nano-interstic gaps after transfer, thus providing stronger and more uniform electromagnetic enhancement. More importantly, in 10 randomly selected test points, the two processes exhibit drastically different signal stability. Figure 5 (A) and Figure 5 As shown in (D), the peak intensities of the 10 spectral curves in Comparative Example 2 fluctuate wildly. R6G was extracted at 610 cm⁻¹. -1 The characteristic peak intensity at a certain point was calculated, and its relative standard deviation (RSD) was as high as 15.58%, indicating that its "hot spot" distribution was extremely uneven and that there was serious signal randomness, which could not meet the requirements for quantitative detection. In contrast, the 10 spectral curves of Example 1 highly overlapped, based on 610 cm⁻¹. -1 The RSD value calculated from the characteristic peak intensity is only 4.21%.
[0067] This fully demonstrates that the thin-film transfer method of the present invention completely overcomes the technical defects caused by traditional direct coating, such as uneven particle nucleation, wide size distribution, and large batch differences. By applying a certain pressure during transfer, not only is high-fidelity bonding between the gold film and the complex three-dimensional ring structure guaranteed, but the SERS chip is also endowed with excellent spectral reproducibility and long-term stability, solving the biggest pain point for SERS technology to move towards practical quantitative applications.
[0068] 4.2 Analysis of the enhancing effect of the substrate ring structure on SERS sensitivity To verify the advantages of the specially designed "ring array protrusion structure" of this invention compared with the traditional planar substrate, the SERS performance of Example 1 (ring array GaN) and Comparative Example 3 (planar GaN without array) was compared while keeping the gold nanoparticle thin film preparation process (interface transfer method) and testing conditions consistent.
[0069] like Figure 4 (A) and Figure 4 As shown in (B), at the same probe molecule concentration, the Raman characteristic peak intensity of Example 1 is significantly higher than that of Comparative Example 3. Quantitative calculations show that the chip of Example 1 at 610 cm⁻¹... -1 The average intensity of the characteristic peak is nearly 1300 higher than that of Comparative Example 3. For example... Figure 5 As shown in (B), the relative standard deviation (RSD) of Comparative Example 3 is as high as 10.96%.
[0070] The circular array designed in this invention features a central aperture (1-2 μm in diameter) that is highly matched to the focused spot size of a 532 nm laser, creating a "light trap" effect at the micro-nano scale. This significantly reduces laser reflection and scattering losses on the substrate surface, maximizing laser utilization. Furthermore, the three-dimensional curved surface structure of the ring induces multiple reflections and plasmonic coupling of the incident light between the bowl wall and the gold nanoparticles, generating a stronger localized electromagnetic field enhancement (i.e., exciting higher-density "hot spots") than a two-dimensional planar structure, thereby improving the SERS signal. Moreover, the protruding structure of the circular array in this invention facilitates the formation of high-density hot spots with similar intensity and uniform distribution. The laser utilization and electromagnetic enhancement effect at any detection point are essentially consistent, significantly reducing signal deviation between multi-point tests.
[0071] 4.3 Synergistic Effect Analysis of Gold Nanoparticle Film Formation Process and Substrate Ring Structure pass Figure 4 , 5 As shown in Table 1, the actual SERS intensity and RSD of Example 1 are greater than the theoretical superposition values. This proves that the array structure and the thin-film transfer process are not simply linearly superimposed, but rather produce a synergistic effect: a single ring array can only slightly improve the SERS signal intensity and has limited effect on reproducibility optimization; while a single interface transfer process can significantly improve sensitivity, but the reproducibility still cannot meet the requirements of quantitative detection. After the two are combined, the three-dimensional confinement effect of the ring array can enhance the uniformity of the gold film arrangement in the interface transfer, and the uniform monolayer gold film in the interface transfer can fully release the optical trap enhancement potential of the ring structure, ultimately achieving a dual improvement in signal intensity and reproducibility. This confirms that the two are not simply performance superpositions, but rather have a synergistic effect of bidirectional promotion.
[0072] Table 1. Chips from Example 1 and Comparative Examples 1-3 at 610 cm⁻¹ -1 The average SERS signal intensity and RSD at the characteristic peak Comparative Example 1 2547 17.16% Comparative Example 2 3097 15.58% Comparative Example 3 6881 10.96% Example 1 8175 4.21% In summary, this invention, through the synergistic effect of the "specially designed circular array protrusion structure" and the "interface thin film transfer process," not only significantly improves the limiting sensitivity of SERS detection, but also fundamentally solves the technical problem of poor signal reproducibility of traditional SERS substrates.
[0073] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0074] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.
[0075] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. A gallium nitride-based metal composite SERS chip, characterized in that, The invention includes a gallium nitride substrate, the surface of which is provided with a periodically arranged array of circular protrusions; a two-dimensional monolayer gold nanoparticle film is attached to the surfaces of the gallium nitride substrate and the array of circular protrusions. The periodically arranged circular array of bumps includes multiple circular bumps, each with an outer diameter of 3~6μm, a central hole diameter of 1~2μm, and a height of 200~1000nm relative to the gallium nitride substrate surface. The two-dimensional monolayer gold nanoparticle film is prepared by liquid-liquid interface self-assembly process and then transferred and bonded to the surface of the gallium nitride substrate and the annular array protrusion structure.
2. The gallium nitride-based metal composite SERS chip according to claim 1, characterized in that, The thickness of the gallium nitride substrate is 1~10 μm; And / or, the distance between two adjacent annular protrusions is 2~6μm; And / or, the average particle size of the gold nanoparticles in the two-dimensional monolayer gold nanoparticle film is 10~80 nm.
3. The gallium nitride-based metal composite SERS chip according to claim 1, characterized in that, The liquid-liquid interface self-assembly process includes: adding a solution containing an assembly agent to an aqueous solution of gold nanoparticles, and forming a two-dimensional monolayer gold nanoparticle film at the liquid-liquid interface by utilizing the principle of liquid-liquid interface self-assembly. The solution containing the assembling agent is formed by dissolving the assembling agent in an organic solvent. The assembling agent is 1H,1H,2H,2H-perfluorodecyl mercaptan and / or dodecyl mercaptan. The organic solvent is obtained by mixing ethanol and n-hexane in a volume ratio of 1:0.2~2.
4. The gallium nitride-based metal composite SERS chip according to claim 1, characterized in that, The surface of the gallium nitride-based metal composite SERS chip also has a hydrophobic modification layer, which is composed of one or more of perfluorodecyltrimethoxysilane, tridecafluorooctyltriethoxysilane, perfluorooctyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.
5. A method for fabricating a gallium nitride-based metal composite SERS chip as described in claim 1, characterized in that, Includes the following steps: S1. A periodically arranged ring array of protrusions is prepared on the surface of a gallium nitride thin film by photolithography combined with etching process; S2. A solution containing an assembly agent is added to an aqueous solution of gold nanoparticles. A two-dimensional monolayer gold nanoparticle film is formed at the liquid interface by utilizing the self-assembly principle of the liquid-liquid interface. S3. The two-dimensional monolayer gold nanoparticle film is transferred from the liquid phase interface to the surface of the gallium nitride substrate and the annular array protrusion structure to obtain a composite SERS chip.
6. The preparation method according to claim 5, characterized in that, Step S1 includes the following steps: (1) Photomask preparation: Design a photomask with a circular array pattern. The circular array pattern is composed of multiple periodically arranged circular structural units. The outer diameter of a single circular structural unit is 3~6 μm, and a circular hollow hole with a diameter of 1~2 μm is provided in the center. The spacing between two adjacent circular structural units is 2~6 μm. The circular rings in the photomask are opaque, while the other areas are transparent. (2) Photolithography process: Photoresist is coated on the surface of the gallium nitride thin film. After spin coating, pre-baking treatment is performed. A photolithography machine is used to bond the photomask and the photoresist layer together to complete the exposure. After exposure, the photomask is removed, the sample is immersed in the developing solution for development, and after being taken out, it is rinsed and dried to form a photoresist ring array mask on the surface of the gallium nitride thin film. (3) Etching and photoresist removal: Dry etching is performed using a plasma etching machine with an etching depth of 200~1000 nm, and only the circular area covered by photoresist is retained; after etching, photoresist removal and cleaning are performed, and after drying, gallium nitride with a periodically arranged circular array of protrusions on the surface is obtained. Alternatively, step S3 includes: immersing the gallium nitride substrate with the annular array protrusion structure prepared in step S1 into the liquid of step S2, lifting the two-dimensional monolayer gold nanoparticle film from bottom to top at the liquid phase interface, and then applying a pressure of 0.3~0.8 N on the film surface and holding it for 5~40 s.
7. The preparation method according to claim 5, characterized in that, The concentration of the aqueous solution of gold nanoparticles is 50~500 μg / mL, and the average particle size of the gold nanoparticles in the aqueous solution is 10~80 nm.
8. The preparation method according to claim 5, characterized in that, The surface of the gallium nitride-based metal composite SERS chip also has a hydrophobic modification layer, and the method for preparing the hydrophobic modification layer includes: S4. Place the composite SERS chip and the glass slide carrying the hydrophobic modifier together in a vacuum drying oven and heat at 100~120℃ for 2~8 h, then cool to obtain the hydrophobic modifier layer. The hydrophobic modifier is one or more of perfluorodecyltrimethoxysilane, tridecylfluorooctyltriethoxysilane, perfluorooctyltriethoxysilane, octadecyltrimethoxysilane, and octadecyltriethoxysilane.
9. The application of the gallium nitride-based metal composite SERS chip as described in claim 1 in surface-enhanced Raman spectroscopy detection.
10. A semiconductor device, characterized in that, Including the gallium nitride-based metal composite SERS chip as described in claim 1.